CFD modelling of CO2 enhanced gasification of coal in a pressurized circulating fluidized bed reactor. (1st October 2018) - Klimanek, Adam; Bigda, Joanna
Abstract: Two CFD models of CO2 -enhanced coal gasification in pressurized circulating fluidized bed reactor were developed and applied to simulate the process and predict syngas composition at the reactor outlet. The models were developed using commercial codes ANSYS Fluent and CPFD Barracuda. The models allowed to predict the outlet syngas composition and give insight into the processes occurring in the reactor. Results of the analyses were compared with experimental data obtained from a small scale test facility. The predicted syngas compositions agreed well with the experimental data, however the local gas composition in some instances were different. The predicted temperature distribution in Fluent agreed well with the experimental data. The examined cases confirmed that addition of CO2 to the gasifying agent in a pressurized reactor can increase the CO yield per unit of feedstock and reduce the oxygen demand. Highlights: CFD modelling of CO2 -enhanced coal gasification in CFB is presented. Two commercial CFD codes were used to develop the models. Results of the simulations were compared with experimental data. Main process parameters were successfully predicted. Selected benefits of CO2 -enhanced gasification were confirmed.